2013
DOI: 10.1371/journal.pone.0055312
|View full text |Cite
|
Sign up to set email alerts
|

Increased HIV Incidence in Men Who Have Sex with Men Despite High Levels of ART-Induced Viral Suppression: Analysis of an Extensively Documented Epidemic

Abstract: BackgroundThere is interest in expanding ART to prevent HIV transmission, but in the group with the highest levels of ART use, men-who-have-sex-with-men (MSM), numbers of new infections diagnosed each year have not decreased as ARTcoverage has increased for reasons which remain unclear.MethodsWe analysed data on the HIV-epidemic in MSM in the UK from a range of sources using an individual-based simulation model. Model runs using parameter sets found to result in good model fit were used to infer changes in HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
198
3
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(216 citation statements)
references
References 43 publications
12
198
3
3
Order By: Relevance
“…However, extended work on the MPES model has indicated that the level of undiagnosed HIV infections was stable between 2001 and 2008 in England and Wales [22]. Furthermore, the method has been found to be robust [22] and its results have been corroborated with other estimates of the size of the undiagnosed MSM population [22,30,31].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, extended work on the MPES model has indicated that the level of undiagnosed HIV infections was stable between 2001 and 2008 in England and Wales [22]. Furthermore, the method has been found to be robust [22] and its results have been corroborated with other estimates of the size of the undiagnosed MSM population [22,30,31].…”
Section: Discussionmentioning
confidence: 92%
“…However, extended work on the MPES model has indicated that the level of undiagnosed HIV infections was stable between 2008 in England and Wales [22]. Furthermore, the method has been found to be robust [22] and its results have been corroborated with other estimates of the size of the undiagnosed MSM population [22,30,31].The threshold for infectivity was defined as a viral load > 1500 copies/mL for two reasons. Firstly, no sexual transmissions were found to occur below this level in an observational study of serodiscordant heterosexuals [19].…”
mentioning
confidence: 99%
“…A third consideration is that a high proportion of new infections come from men who are not yet diagnosed, and in many cases men who have only just been infected. [12][13][14] This might seem to limit the influence that ART can have in reducing new HIV infections in MSM. We should also consider how high the rate of HIV testing is, and how rapidly those who are infected become diagnosed and linked to care.…”
Section: Synopsismentioning
confidence: 99%
“…The work was reported in two papers. 1,14 The first concentrated on understanding influences on the epidemic up to 2012 and described the structure and calibration of the model of HIV transmission, progression and the effect of ART that was developed for this. The model was then used to help us understand the relative influences of sexual risk behaviour change, rates of HIV testing and ART-induced virological suppression on HIV infection incidence up to 2012.…”
Section: Sexual Risk Behaviour In People Enrolled In the Start Trialmentioning
confidence: 99%
See 1 more Smart Citation